2010
DOI: 10.1109/tasc.2010.2041218
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the ${^{1}{\rm H}}$ NMR Relaxation Enhancement Produced by Bacterial Magnetosomes and Synthetic Iron Oxide Nanoparticles for Potential Use as MR Molecular Probes

Abstract: Iron oxide nanoparticle, named synthetic magnetite, as contrast agent has been widely used in clinical MRI. Recently, a new magnetite nanocrystal, called magnetosome, has been found in magnetotactic bacteria. Physicochemical and magnetorelaxo-metric characterization of bacteria magnetosomes and iron oxide nanoparticles are investigated. Bacterial magnetosomes have the larger mean aggregate size, better dispersion and obviously stronger ferromagnetism compared to synthetic magnetites. The samples of several con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“… 366 , 367 Additionally, the biosynthesis of magnetosomes from MTBs is highly controlled and results in particles with uniform size, shape, dispersion, and even magnetization, whereas magnetic NPs that are synthesized by chemical precipitation are often superparamagnetic and nonuniform with respect to the aforementioned parameters. 368 …”
Section: Biological Methods To Improve Nm Delivery To Tumorsmentioning
confidence: 99%
“… 366 , 367 Additionally, the biosynthesis of magnetosomes from MTBs is highly controlled and results in particles with uniform size, shape, dispersion, and even magnetization, whereas magnetic NPs that are synthesized by chemical precipitation are often superparamagnetic and nonuniform with respect to the aforementioned parameters. 368 …”
Section: Biological Methods To Improve Nm Delivery To Tumorsmentioning
confidence: 99%
“…Such high values of r 2 can be reached with the magnetosomes. Indeed, it has been shown that both magnetosomes enclosed in a gel and ferrimagnetic nanoparticles different from ferridex and with similar properties than the magnetosomes possess values of r 2 as high as 1175 and 324 mM s −1 , respectively (Hu et al, 2010 ; Lee et al, 2011 ). These two values are larger than the value of r 2 ~ 133 mM s −1 found for chemically synthesized nanoparticles ferridex, which are currently approved and tested in the clinic as contrast agents for MRI application (Lee et al, 2011 ).…”
Section: Applications Of Magnetosomes In Mri Magnetic Hyperthermia mentioning
confidence: 99%
“…Therefore, only a limited number of MTB can be isolated as a pure culture, hence due to the low cell densities, the sufficient numbers of magnetosomes cannot be purified which further hampers industrial applications. The emerging opportunities relating to MTB are high-data storage, MRI, treating disease by a mannose-binding lectin, DNA discrimination analysis, drug delivery, they act as carriers for enzymes, nucleic acids, antibodies, biosensors and waste-water treatment [13,28].…”
Section: Discussionmentioning
confidence: 99%